Knowledge of First Aid Measures in Dental Trauma: A Survey of Teachers in the Province of Seville, Spain - David Ribas Perez; Rosmery Olivera; Asuncion Mendoza Mendoza; Beatriz Solano Mendoza (Children, 2022)
The high incidence of childhood dental trauma requires childcare professionals to have basic notions of dental first aid. The aim of this study is to assess the level of knowledge and aptitude (defined as the ability to operate competently in a given activity) of early childhood, primary, and/or secondary education teachers from Seville (Spain) referred to first aid measures in dental trauma. A descriptive study was conducted. The study sample consisted of 442 teachers (334 women and 108 men) coinciding proportionately with the study target population in terms of gender distribution, type of center, and teaching level. A specifically designed questionnaire was used. Most of the participants (88.5%, n = 391) exhibited poor knowledge and aptitude, 11.5% (n = 51) showed a medium level of knowledge and aptitude, and none were categorized as having a high knowledge and aptitude. As a conclusion, teachers in the province of Seville (Spain) showed marked deficiencies in their level of knowledge and aptitude referred to the adoption of first aid measures in dental trauma among their pupils.